TEACHING TO LEARN: CURRENT TRENDS IN HIGHER EDUCATION - Solís Umaña, Mario (2018)
The paper critically examines some current pedagogical methodologies, particularly those related to the so-called “deep”, “strategic” and “surface” learners. The paper discusses the pros and cons of the above typology and seeks to shed light on the theoretical and meth- odological connections in relation to student “profiles” and towards the achievement of the fundamental goals in higher education.